Thin film sputter-deposition of AlN crystals in oxygenated chamber: a pilot study - Muhammad Izzuddin Abd Samad; Syazwani Izrah Badrudin; Marwan Mansor; Nafarizal Nayan; Ahmad Shuhaimi Abu Bakar; Mohd Zamri Yusop; Rhonira Latif (Materials Research Express)
Aluminium nitride (AIN) is a promising thin film electrical insulation material layer in electronic devices. The magnetron sputtering method is usually employed to sputter-deposit AlN thin film on silicon (Si) substrate using a pure aluminium (Al) metallic target in a low base pressure vacuum condition. In many cases, the thin film deposition of high quality AlN crystals requires the application of heat and bias to the substrate, highly pure nitrogen reactant gas, argon sputtering gas and Al target, low sputtering pressure, high sputtering power, post-deposition AlN annealing, ultra-low base pressure of the sputtering chamber and a distinctive crystal orientation of the nucleation layer or substrate underneath. In our work, the utilisation of AlN ceramic target instead of pure Al metallic target has allegedly facilitated the growth of AlN crystals without the need to conform to these requirements. Non-amorphous AlN〈100〉 and AlN〈002〉 thin film crystals have been successfully sputtered from AlN ceramic target on Si〈100〉 substrate in a relatively high sputtering chamberbase pressure and at a moderate 200 W - 250 W of sputtering power. Additionally, 250 W of sputtering power has been observed to assist in the growth of AlN〈002〉 crystals. The presence of AlN〈002〉 may have reduced the leakage/tunnel current density in AlN thin film layer to 46.33 pA cm ^−2 and modified the small-scale surface height characteristics. A high degree of AlN〈002〉 crystallisation may suggest good electrical insulating properties in AlN thin film layer, which can be applied in electronic devices that critically require a low leakage current specification.